PERAN ANTIGEN NS1 DENGUE TERHADAP PENGHITUNGAN TROMBOSIT DAN PENAMPAKAN (MANIFESTASI) KLINIS PENJANGKITAN/PENULARAN (INFEKSI) VIRUS DENGUE - J Nugraha; T.E Widijatmoko (Indonesian Association of Clinical Pathologist and Medical laboratory, 2010)
Dengue virus infection has become the major health problem in Indonesia. Dengue haemorrhagic fever is a part of dengue virus infection. 95% of this disease commonly affects children less than 15 years. However, in the last five years the incidence of DHF hasalso increased in adults. In 2008, the case fatality rate of DHF was 0.99% in East Java and 0.47% in Surabaya. The diagnosis of DHFis based on the 1997 WHO criteria. Thrombocytopenia is a haematological abnormality occurring in DHF. There is a hypothesis aboutthe role of non-structural 1 antigen (NS1 antigen) during initial virus replication leading to immunological reaction manifestationin thrombocytopenia. To analyze the role of NS1 antigen dengue to platelet count and clinical manifestations to know the degree ofdengue virus infection. This study used a cross-sectional design. The samples are comprised of 52 patients with dengue fever anddengue haemorrhagic fever grade I until III hospitalized at Tropical Disease Ward, Dr.Soetomo Hospital, and Surabaya. Data wereanalyzed using Mann-Whitney test, t-two sample test (p = 0.05). The result of this study using Mann-Whitney test show no difference between NS1 antigen dengue with the clinical manifestations in dengue virus infection (p = 0.882). Analysis using t-two sample test showed a significant difference between NS1 antigen dengue positive and NS1 antigen dengue negative with a change in platelet count (p = 0.006). Although, the test showed no significant difference between NS1 antigen dengue and the platelet count in dengue virusinfection (p = 0.062). There were found no significant association between NS1 dengue antigen with platelet count and clinicalmanifestations in dengue virus infection.